Reduction of vibration transmission and flexural wave propagation in composite sandwich panels - Motipalli, V. V. Satish K. (Kansas State University, 2015)
Thin walled structures such as plates and shells have application in many fields of engineering because these structures are light weight and can support large loads when designed suitably. In real world, loads may cause these structures to vibrate which can be undesirable causing fatigue and failure of the structure. Such undesirable vibrations need to be reduced or eliminated. In this work, analytical studies of flexural wave propagation for idealized geometries are conducted and finite element method (FEM) is used to explore the effects of composite panel designs of finite size for the reduction of vibration transmission. In the analytical studies, the influence of the material properties on the reflection and transmission characteristics are explored for an infinite bi-material plate, and infinite plate with a strip inhomogeneity. In the analytical study of an infinite thin plate with a solid circular inclusion, the far and near field scattering characteristics are explored for different frequencies and material properties. All the analytical studies presented here and reported in the literature consider infinite plates to characterize the flexural wave propagation. Obtaining closed form solutions to characterize the flexural wave propagation in a finite plate with inclusions is mathematically difficult process. So, FEM is used to explore the composite panel designs. The understanding gained about the material properties influence on the flexural wave propagation from analytical studies helped with the choice of materials for FEM simulations. The concept of phononic crystals is applied to define the design variations that are effective in suppressing vibration transmission. Various design configurations are explored to study the effects of various parameters like scatterer’s material properties, geometry and spatial pattern. Based on the knowledge gained through a systematic parametric study, a final design of the composite sandwich panel is proposed with an optimum set of parameters to achieve the best vibration reduction. This is the first study focused on reducing vibration and wave transmission in composite rotorcraft fuselage panels incorporating the concept of phononic crystals. The optimum sandwich panel design achieved 98% vibration transmission reduction at the frequency of interest of 3000 Hz.
Keywords: Flexural wave propagation; Vibration reduction; Phononic crystals; Finite element method; Mechanical Engineering (0548)